A DNA barcoding approach for identification of hidden diversity in Parmeliaceae (Ascomycota): Parmelia sensu stricto as a case study. (12th November 2015) - Divakar, Pradeep K.; Leavitt, Steven D.; Molina, M. Carmen; Del‐Prado, Ruth; Lumbsch, H. Thorsten; Crespo, Ana
Abstract : Accurate specimen identification is challenging in groups with subtle or scarce taxonomically diagnostic characters, and the use of DNA barcodes can provide an effective means for consistent identification. Here, we investigate the utility of DNA barcode identification of species in a cosmopolitan genus of lichen‐forming fungi, P armelia (Parmeliaceae). Two hundred and two internal transcribed spacer (ITS) sequences generated from specimens collected from all continents, including Antarctica, were analysed, and DNA barcodes of 14 species of P armelia s.s. are reported. Almost all species show a barcode gap. Overall, intraspecific divergence values were lower than the threshold previously established for Parmeliaceae. However, the mean and range were elevated by deep barcode divergences in three species, indicating the likely occurrence of overlooked species‐level lineages. Here, we provide a DNA barcode reference library with well‐identified specimens sampled worldwide and sequences from most of the type material to enable easy and fast accurate sample identification and to assist in uncovering overlooked species in P armelia s.s. Further, our results confirm the efficiency of the ITS region in the identification of species of P armelia s.s . © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 180, 21–29.